(untitled) (Scientific journal of the Fergana State University, 2023)
Linguistic ecology has been shaped in response to the need of analyses of the underlying trends, and, if possible, in obtaining objective information about the state of the national language in order to predict "language disorders" and to avoid them. Linguistic ecology is of particular social importance due to the comprehensive study of the language environment and the specific nature of society. Conservation of the language’s ability to express the human environment in a specific way is manifested in environmental linguistics.